A Cat Café Christmas - Gary, Codi (Forever, 2022)
"Kara Ingalls has come to California for a fresh start. Along with her friend Charity, she opens The Meow and Furever Cat Café. With Charity in charge of the baking and Kara caring for the rescues, they've got this! Except that Kara's dream job isn't as easy as it seems when the rent comes due and the special needs cats stay too long. Enter Ben Reese. As a dog lover, he doesn't seem qualified to help, but as a marketing professional, he's just what Kara can't afford to ignore. He's bossy and pushy and nerdy...but she finds herself inviting him to their Friendsgiving anyway. Where unlikely sparks fly with this cat hater. Now Ben has implemented a plan to find homes for all the felines in twenty-five days, and he's even doing his part by fostering a tiny kitten with a huge personality. Can a dog person be converted to a cat lover and save the cat café by Christmas? And the more important question is whether Ben and Kara can set aside their differences to be together for a purr-fect holiday"--